Visible sound and audible movements: the Ca trù singer’s bamboo slab - Jaehnichen, Gisa (Pusat Kebudayaan, Universiti Malaya, 2013)
The ca trù singer’s bamboo slab is considered to be one of the most complex musical instruments in North Vietnamese music traditions. Its playing is not a mere percussive accompaniment of the singer. It is one of the very few tools used for bodily expression in this genre that usually does not allow for strong emotional movements by neither the singer nor the lutenist, of which a ca trù ensemble mainly consists. Thus the movement patterns realised by playing the bamboo slab carry multiple musical and performative meanings on which the paper will focus on. In a traditional performance setting, the co-educated audience can follow the structure of the song and the textual essence implied by movements of the singer’s hands playing the bamboo slab. Inherent knowledge of gestures and their dynamics gives the performance its transparency and contributes indispensably to the communication among the musicians and between the musicians and their audience. However, the rules of structuring percussive patterns and intended movements in this highly sophisticated musical genre are very complex and multilayered. In this paper, an attempt is undertaken to analyse these rules from the perspective of the singer cum bamboo slab player. Accordingly, an overview about local researches carried out on ca trù and the relationship between musical performance and its physical embodiment is offered to summarize the level of present knowledge among academicians and musicians in North Vietnam.